THE COLEGIO DE SAN NICOLAS DURING THE SECOND HALF OF THE NINETEENTH CENTURY. FROM EDUCATIONAL AREA TO SOCIAL EXPECTATION (Tzintzun, Revista de Estudios Históricos, 2022)
The aim of this article is to analyze the discursive construction of a socialrepresentation of the “nicolaitas” (regents, professors and students) fostered bythe internal regulations of the Colegio de San Nicolás de Hidalgo. The mainsupplying of this work are, therefore, the regulations of the Colegio de San Nicolasin Morelia. At the same time, some communications between the secretary ofthe State Government and that of the campus were reviewed, as well as somepress releases. The arguments are constructed based on Pierre Bourdieu’sapproaches to representation and with some guidelines to approach the rulesand practices offered by the analysis from the viewpoint of everyday school life.The main question that has been raised is how much the regulations weighed atthe moment of interacting outside the school. Through discourse analysis, wereflect on how they sought to be perceived in terms of practices and values thatthey considered as their own, but also attached to the regulations.
Keywords: behavioral expectations; nicolaitas”; social presence; everyday life